India's State-Owned Enterprises - Agarwal, Ruchir (IMF Working Papers; Working Paper, 2022)
India's recently announced privatization strategy can facilitate a change in the composition of the public sector balance sheet toward high-return public sector investments in infrastructure and human capital where there is a clear role for government, leaving commercially viable companies for the private sector. Against this background, this paper provides a description of the SOE sector in India, consider different criteria which can inform the scope and rationale for privatization. It also highlights takeaways from international experience with privatization, highlights the importance of improved governance and oversight of SOEs and showcases analytical tools that can help analyze risks from SOEs. While this paper focuses on India, the framework for SOEs developed in this paper can be used to evaluate SOEs policy options in other countries.